2021
DOI: 10.3390/ijerph18136695
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Epidemics and Pandemics on the Mental Health of Healthcare Workers: A Systematic Review

Abstract: Background: There is increasing evidence that healthcare workers (HCWs) experience significant psychological distress during an epidemic or pandemic. Considering the increase in emerging infectious diseases and the ongoing COVID-19 pandemic, it is timely to review and synthesize the available evidence on the psychological impact of disease outbreaks on HCWs. Thus, we conducted a systematic review to examine the impact of epidemics and pandemics on the mental health of HCWs. Method: PubMed, PsycInfo, and PsycAr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
93
2
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 116 publications
(127 citation statements)
references
References 94 publications
(402 reference statements)
7
93
2
4
Order By: Relevance
“…With regard to our first research question concerning the levels of stress and symptoms of anxiety and depression nurses experienced, our findings showed that nurses who provided direct patient care during the COVID-19 pandemic in the Canary Islands, Spain, reported a considerable prevalence of perceived stress and symptoms of anxiety and depression. These results were in line with recent studies that revealed that the prevalence of anxiety and depression disorders was relatively high among healthcare workers during the COVID-19 pandemic [ 11 , 33 , 34 , 35 ]. Our results confirmed our first hypothesis, which posited that nurses’ perceived stress was positively correlated with symptoms of anxiety and depression.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…With regard to our first research question concerning the levels of stress and symptoms of anxiety and depression nurses experienced, our findings showed that nurses who provided direct patient care during the COVID-19 pandemic in the Canary Islands, Spain, reported a considerable prevalence of perceived stress and symptoms of anxiety and depression. These results were in line with recent studies that revealed that the prevalence of anxiety and depression disorders was relatively high among healthcare workers during the COVID-19 pandemic [ 11 , 33 , 34 , 35 ]. Our results confirmed our first hypothesis, which posited that nurses’ perceived stress was positively correlated with symptoms of anxiety and depression.…”
Section: Discussionsupporting
confidence: 92%
“…Recent meta-analysis studies have revealed the strong impact that the COVID-19 outbreak has had on people’s psychological wellbeing and mental health [ 11 , 33 ], which increases the urgency of addressing mental health during and after this global health crisis. Through their daily routines, as well as during the exceptional circumstances brought about by the COVID-19 pandemic, nurses have a frontline position that is critical to the function of healthcare systems, as they are responsible for providing comprehensive care to all types of patients.…”
Section: Discussionmentioning
confidence: 99%
“…As of May 20, 2021, there have been 163,738,674 reported cases of COVID-19 and 3,384,750 deaths worldwide ( ECDC, 2021 ). The mental health impact on healthcare and social care workers is of particular concern ( Chigwedere et al., 2021 ; Gold, 2020 ). Specific stressors on Healthcare workers and social care workers include worries about their own and their family's infection risk and the stigma this may entail ( Bruffaerts et al., 2021 ; Muller et al., 2020 ; Qi et al., 2020 ; Xu et al., 2021 ), concerns about the availability and adequacy of personal protective equipment ( Bruffaerts et al., 2021 ; Chung and Yeung, 2020 ), increased workloads and stress ( Hong et al., 2021 ), having to make difficult decisions about prioritising care for seriously ill patients (moral injury) ( Mortier et al., 2021 ; Williamson et al., 2020 ), and lack of support from colleagues and authorities ( Hong et al., 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Fatigue refers to a sub-health state without specific symptoms, such as psychological and physical fatigue ( 1 ). Work-related fatigue harms the efficiency, health, and safety of the nurses by producing symptoms, such as headache, dizziness, anxiety, depression, compulsion, and insomnia ( 2 4 ). It could also increase the risk of injures and medication errors of nurses, which are compounded by poorly designed working space and environment ( 5 7 ).…”
Section: Introductionmentioning
confidence: 99%
“…The overwhelming workload does not only produce physical exhaustion, but also increase the psychological burden ( 15 ). During COVID-19, nurses usually experienced depression, exhausted stress, insomnia, and other negative emotions ( 2 , 3 ). The long-term exposure to medication procedures such as intubation and nebulization also leads to the high percentage of fatigue by fear of the hospital-acquired infections ( 16 , 17 ).…”
Section: Introductionmentioning
confidence: 99%